A new species of Naryciodes Matsumura, 1931 (Lepidoptera: Limacodidae) from Korea - Sohn, Jae-Cheon; Choi, Sei-Woong (Zootaxa, 2017)
The genus Naryciodes was originally proposed as a monobasic genus (type species: Naryciodes posticalis Matsumura) by Matsumura (1931) in Tineidae. About fifty years later, the genus was transferred to Limacodidae by Inoue (1982) because the larvae possess an autapomorphic character of Limacodidae: the lack of crochets on the prolegs (Epstein et al. 1999).